2005
DOI: 10.1007/11586821_3
|View full text |Cite
|
Sign up to set email alerts
|

Improved Decoding of Interleaved AG Codes

Abstract: Abstract. We analyze a generalization of a recent algorithm of Bleichenbacher et al. for decoding interleaved codes on the Q-ary symmetric channel for large Q. We will show that for any m and any the new algorithms can decode up to a fraction of at least βm βm+1 (1−R−2Q −1/2m )− errors, where β = ln(q m −1) ln(q m ) , and that the error probability of the decoder is upper bounded by O(1/q n ), where n is the block-length. The codes we construct do not have a-priori any bound on their length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…interleaved AG codes considered in [3]. Thus C(X, P, E) generalizes these two previously known codes simultaneously.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…interleaved AG codes considered in [3]. Thus C(X, P, E) generalizes these two previously known codes simultaneously.…”
mentioning
confidence: 81%
“…Generalizing the algorithm for interleaved AG codes given in [3], Savin proposed a decoding algorithm for these vector bundle codes when E satisfies a property called weak stability and has shown that we can correct all errors with < t * − g/2, where g denotes the genus of X and t * is the designed correction capacity defined by…”
mentioning
confidence: 99%
“…Using these codes, we will get efficient implementations of one-time memories. There are several known constructions for codes that approach the capacity of the q-ary symmetric channel, and are efficiently decodable [22,23,24]. To illustrate how these techniques can be applied in our setting, we will describe one simple approach, which is based on erasure coding and error detection [23].…”
Section: Efficient Implementations Of One-time Memoriesmentioning
confidence: 99%
“…Our OTM's can be constructed using any code that satisfies two simple requirements: the code must be linear over GF (2), and it must approach the capacity of the q-ary symmetric channel. We show one such code in this paper; several more sophisticated constructions are known [22,23,24]. ) We will describe our OTM construction in the following section.…”
Section: Introductionmentioning
confidence: 99%
“…To assess this question to some extent, we follow the usual approach by investigating a weaker variant of the scheme. 11 More precisely, we consider a variant where the used code is known to the attacker, i.e., the attacker is given (eventually) a basis for the vector space V 0 while V err remains secret. This allows for the following insights:…”
Section: Decisional Synchronized Codewords Problem (Dscp)mentioning
confidence: 99%